Penerapan Kaidah Fiqh Manajemen Laba Pada Lembaga Keuangan Syariah Dalam Perspektif Islam - Iva Lisrohkhati; Erfi Dwi Mutahharo Tunnisak; Alfina Ratna Wardani; Agus Eko Sujianto (Universitas 45 Surabaya, 2023)
The purpose of this study is to determine the application of fiqh related to earnings management in Islamic financial institutions. The method used in this research is a qualitative method. The presence of fiqh rules is needed to solve problems in a broad scope, even in Islamic financial institutions, especially in earnings management. Either in its application or regarding rules that are restrictive in lawful or not prohibited implementation. Usually in Islamic financial institutions, mudharabah and musyarakah are contracts that are commonly used for transactions in Islamic banks. The application of fiqh principles in earnings management is proven to be significantly applied, through its application which must comply with Islamic ethical provisions and be based on the Islamic spirit. In the practice of earnings management, all parties must behave according to sharia provisions or according to sharia principles.